Peningkatan Pemahaman Rumus Geometri Melalui Pendekatan Realistik di Kelas V SD Negeri 1 Baiya - Lufian, Lufian (Jurnal Kreatif Tadulako Online, 2016)
The classroom action research was carried out in order to : (1) make students easier in understanding geometrical formulas; (2) raise the studentsâ achievement about geometrical formula understanding and its application especially in the case of plane area. : (3) motivate the students to understand geometrical formulas; and (4) make the teaching-learning of understanding geometrical formulas would be more effective. The research was carried out at the fith grade of state elementary school called 1 Baiya. The Research was carried out in three cycles with each sycle consisting of planning, actuating , observing and reflecting. The research data were collected by instruments namely the achievement test, observation and interview. Quantitative data were analysed by descriptive statistics; that was by searching for the mean and by a test of difference, where as qualitative data were analysed by an interpretative descriptive. The research finding showed that the teaching of the plane area formulas of rectangulars and triangles by realistic approach could raise the studentsâ eagerness and motivation in learning , understanding as well as applying the plane area. It could be concluded that the teaching method applied could raise studentsâ achievement in learning the plane area formula especially rectangulars and triangels. In othe words, the teaching of geometrical formulas by realistic approach could raise the studentsâ understanding about geometrical formulas. Key words: Â Â Â Â  Understanding geometrical formulas, realistic approach, and the elementary school.